Node centrality metric based caching mechanism in content-centric network - Yue-ping CAI; Jun LIU; Xin-wei FAN (Tongxin xuebao)
In order to reduce the cache redundancy as well as increase the cache hit ratios in content-centric networks,the node centrality metric based caching mechanism (CMC) was proposed.CMC utilized controllers to obtain the topology of the whole network and the idle rate of cache space.According to the connection relation of the topology,the degree centrality,closeness centrality and betweenness centrality of nodes were calculated.When CMC choose the caching nodes,it took the three metrics and the idle rate of cache space into account.Simulation results show that CMC can effectively increase the cache hit ratios and reduce the content fetching hops and average request delay compared with the traditional routing algorithms in CCN.